'In the Friars': The Spatial and Cultural Geography of an Indoor Playhouse. Issue 88 (October 2015) - Sanders, Julie
This article tells the 'biography' of one particular indoor London playhouse, the Blackfriars, and the precinct and neighbourhood in which it operated. The methodology seeks to narrate the story of different seventeenth-century commercial theatres as spaces and places by means of what abutted them in terms of people, landscapes, traffic, noise, smell, sights and actions. The article looks in detail at three particular locales that abutted the Blackfriars Theatre – the Royal Wardrobe, the Bridewell Prison and the River Thames – and reconstructs lived experiences from the traces they have left in street patterns, in architecture, and significantly, in drama.